Production of liquid biofuel from sludge palm oil (SPO) using heterogeneous catalytic pyrolysis - Ali, S,H; M. Hafriz, R.S.R; Shamsuddin, A. H.; Salmiaton, A. (Tamkang University, 2022)
Sludge palm oil (SPO) is one of the wastes produce in palm oil industry. The discharge of sludge palm oil together with palm oil mill effluent has created major problem due to its difficulty in treatment process. The purpose of this study is to investigate the feasibility of sludge palm oil to be used as a raw material for biofuel production. The study was carried out via the pyrolysis process using heterogeneous catalyst. The catalyst used in this reaction was Malaysian dolomite catalyst. This experimental study evaluated the best condition for reaction process based on the interaction effects between operating temperatures and reaction times. The condition for the reaction parameters investigated are as followed: operating temperatures of 350°C, 400°C, and 450°C, reaction times of 30. 45 and 60 minutes, 100cc/min of nitrogen flow rate and 5.0wt/wt catalyst loading. Very low sludge palm oil conversion was found at temperature 350oC even at longer reaction times. Longer reaction times gave higher palm sludge oil conversion at operating temperature of 400oC with the range of conversion between 45.7 to 58.3 wt.. At temperature 450oC, the conversion achieved an average of 93.1 ± 1.0 wt.. Only slight change at longer times was observed at this temperature. At temperature 400°C and 45 min reaction times, the pyrolysis oil obtained from the process contained the highest hydrocarbon content (83.90) and lowest oxygenated compound content (16.10), even though the conversion was lower than at 450°C. product selectivity in terms of diesel group was highest at 400°C. Thus, with further improvement in catalyst modification together with optimized operating conditions, sludge palm oil can be used as a feedstock in the catalytic pyrolysis for biodiesel, biogasoline and biokerosene production.